SLE non-coding genetic risk variant determines the epigenetic dysfunction of an immune cell specific enhancer that controls disease-critical microRNA expression - Guojun Hou (Nature Portfolio, 2021)
Enhancers shape gene expression patterns and are involved in disease pathogenesis. Here the authors demonstrate a strategy to screen functional regulatory elements for non-coding RNAs ― illustrated with miR-146a ― and link autoimmune disease risk genetic variants to autoimmune disease etiology.